Characteristics of calcium intake in nursing home residents in Zagreb - Cvijetić, Selma (Array, 2020)
Elderly people, especially those who live in nursing homes, are at high risk for getting osteoporosis and bone fractures. Knowing that an adequate calcium intake is important for prevention and therapy of osteoporosis, we aimed to estimate calcium intake in old people living in nursing homes in Zagreb. In a cross-sectional study, calcium intake was estimated using previously validated food frequency questionnaire especially designed for calcium intake, among 292 nursing homes residents (232 women and 60 men), mean age 82.4±6.5 years. Mean dietary calcium intake in men was 653±297 mg/day and in women 528±279 mg/day (p=0.004). Only 10 % of women and no men were taking calcium supplements. Calcium intake below the 750 mg/day was present in 67.3 % of men and 77.5 % of women. Very low calcium intake, below the half of the recommended value, was present in 18.3 % of men and 31.0 % of women. Milk and dairy products were the main source of calcium intake in our study and contributed more than 80% of total daily calcium intake. No significant correlation was found between the body mass index and calcium intake in both genders. We conclude that the mean calcium intake in nursing home residents was below the recommended values.